What influences patients' decisions regarding palliative care in advance care planning discussions? Perspectives from a qualitative study conducted with advanced cancer patients, families and healthcare professionals. (December 2019) - Lin, Cheng-Pei; Evans, Catherine J; Koffman, Jonathan; Sheu, Shuh-Jen; Hsu, Su-Hsuan; Harding, Richard
Background: The concept of advance care planning is largely derived from Western countries. However, the decision-making process and drivers for choosing palliative care in non-Western cultures have received little attention. Aim: To explore the decision-making processes and drivers of receiving palliative care in advance care planning discussions from perspectives of advanced cancer patients, families and healthcare professionals in northern Taiwan. Method: Semi-structured qualitative interviews with advanced cancer patients, their families and healthcare professionals independently from inpatient oncology and hospice units. Thematic analysis with analytical rigour enhanced by dual coding and exploration of divergent views. Results: Forty-five participants were interviewed ( n = 15 from each group). Three main decision-making trajectories were identified: (1) 'choose palliative care' was associated with patients' desire to reduce physical suffering from treatments, avoid being a burden to families and society, reduce futile treatments and donate organs to help others; (2) 'decline palliative care' was associated with patients weighing up perceived benefits to others as more important than benefits for themselves; and (3) 'no opportunity to choose palliative care' was associated with lack of opportunities to discuss potential benefits of palliative care, lack of staff skill in end-of-life communication, and cultural factors, notably filial piety. Conclusion: Choice for palliative care among advanced cancer patients in Taiwan is influenced by three decision-making trajectories. Opinions from families are highly influential, and patients often lack information on palliative care options. Strategies to facilitate decision-making require staff confidence in end-of-life discussions, working with the patients and their family while respecting the influence of filial piety.